Psidium schenckianum (Myrtaceae): lectotypification, a new synonym and notes on a typical Caatinga species - Tuler, Amélia Carlos; Conceição, Lázaro Henrique Soares De Moraes; Costa, Grênivel Mota Da; Proença, Carolyn Elinore Barnes (Phytotaxa, 2023)
N/A